Globalization, FDI and modernising management practices - Csaba Makó; Marc Ellingstad (Journal for East European Management Studies, 2000)
This article deals with the role of Foreign Direct Investment in connection with the globalization process. Two sets of changes are taking place worldwide. First: the increasingly common expectations of investors, managers, and even consumers in countries and regions with widely varied economic and cultural histories as a result of FDI. Second: This change is harder to grasp. It is the reaction to the first change and the religion of uniform global capitalism which is being questioned and challenged. This paper is aimed to provide perspectives on various possibilities and limitations of FDI to serve as the engine of modernisation in the Hungarian economy. – – In diesem Artikel wird die Rolle des Foreign Direct Investment (FDI) in Verbindung mit dem Prozess der Globalisierung diskutiert. Weltweit zeigen sich dabei zwei Veränderungen. Erstens: Hier geht es um die in immer größerem Maße gemeinsamen Erwartungen an FDI von Investoren, Managern und sogar Konsumenten in Ländern mit verschiedensten ökonomischen und kulturellen Hintergründen. Zweitens, und diese Veränderung ist schwieriger zu erfassen: Die Reaktion auf die erste Veränderung ist eine Infragestellung der weltweiten Gleichartigkeit des Kapitalismus. Es wird in dieser Arbeit versucht, verschiedene Perspektiven und Grenzen von FDI aufzuzeigen, die als Antrieb für die Modernisierung der ungarischen Wirtschaft dienen.
Keywords: 650